Socioeconomic Differences in Cigarette Smoking and Alternative Tobacco Product Use Among Adolescents in a School-Based Smoking Preventive Intervention: Findings From the Second Year of the X:IT II Study - Kjeld, Simone Gad; Lund, Lisbeth; Andersen, Susan; Bast, Lotus Sofie (Frontiers in Public Health, 2022)
Background: Health interventions may differently impact adolescents from diverse backgrounds. This study examined whether a smoking preventive intervention was equally effective in preventing cigarette smoking and use of alternative tobacco products (ATPs, i.e., snus, e-cigarettes, and waterpipe) among students from different socioeconomic backgrounds, i.e., occupational social classes (OSC). Methods: Data was from the school-based intervention X:IT II targeting 13- to 15-year-olds Danes. The intervention focused on three main components: smoke-free school time, smoke-free curriculum, and parental involvement. In total, 46 schools were included at baseline (N=2,307, response rate=86.3%). Using a difference-in-differences approach, changes in current smoking and ever use of ATPs were estimated among students in high versus low OSC at second follow-up. Analyses were based on available cases (N=826) and multiple imputations of missing data at the second follow-up (N=1,965). Results: At baseline (age 13), 1.0% of students from high OSC and 4.8% from low OSC currently smoked cigarettes, while this was the case among 24.5% and 25.6%, respectively, at the second follow-up (age 15). Estimates indicated that social inequalities in current smoking diminished over time (p <0.001). Regarding ATPs, 10.0% of high OSC students and 13.9% of low OSC students had ever used ATPs at baseline, while at second follow-up, 46.8% and 60.8%, respectively, had ever used ATPs. Estimates indicated that social inequalities in ever use of ATPs widened over time (p <0.001). Conclusions: The X:IT II intervention seemed to diminish socioeconomic disparities in smoking over the study period. Meanwhile, social inequalities in ever use of ATPs increased. Therefore, besides focusing on narrowing the social disparities in cigarette smoking, future efforts may, to a larger extent, focus on adolescents' use of ATPs.